Development Of Video-Based Learning Media With Videoscribe Application On Liquid Pressure Materials Class VIII A MTs Miftahul Huda Batukasur - Sihabul Fahmi, Syifa; Hayati, Nur; Kuswanti, Nur (Riviera Publishing, 2022)
Based on the results of observations and interviews with several teachers and students conducted on April 13, 2020 in class VIII A of MTs Miftahul Huda Batukasur, it shows that science learning uses learning facilities in the form of a blackboard and does not use interesting media for students. In the learning process, it can be seen that students' interest in science lessons is still low. The aims of this study were to determine: (1) To determine the process of developing learning media and the feasibility of video-based learning media with the videoscribe application on Pascal's legal liquid material. This type of research is research and development (R&D). This model consists of analysis, design, and development. The type of data obtained is qualitative data in the form of the process of developing video-based learning media with the videoscribe application and quantitative data in the form of validation results of video-based learning media with the videoscrib application. Collecting data in this study using a questionnaire research method. This development research is in the form of a video-based learning media product with a videoscribe application on Pascal's law fluid pressure material for class VIII A MTs Miftahul Huda Batukasur. The results of this development research indicate that video-based learning media with the videoscribe application on liquid law material for class VIII A MTs Miftahul Huda Batukasur are in the appropriate category. the results of the validation of the media expert obtained the percentage of the graphic feasibility component of 73%, the result of the validation of the material expert obtained the percentage of the graphic feasibility component of 55%, the validation result by the science teacher obtained the percentage of the graphic feasibility component of 77%.